Pinjaman Online di Era Digital: Tantangan dan Peluang Bagi Mahasiswa di Kabupaten Asahan - Saputra, Endra; Muhazir, Ahmad; Tanjung, Nurya Anggi Br (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The objective of this study is to provide education and understanding, as well as to identify the challenges and opportunities of online loans in the Digital Era, particularly for students in Asahan Regency. This study employs a Mixed Method approach, combining quantitative research with an analytical cross-sectional design and qualitative research to strengthen the quantitative data through semi-structured interviews, also known as focus group discussions (FGD). The population of this study consists of university students in Asahan Regency, using primary data collected via questionnaires. The sample size used in this study is 100 respondents. Data processing is conducted using SPSS software, with multivariate analysis through multiple regression. Research findings explain that there is not a positive and significant correlation between financial literacy and self-efficacy on student decisions to use online loans, but for user behavior and financial conditions there is positive and significant correlation on students' decisions to use online loans.
Keywords: Self-Efficacy; Fintech; Financial Literacy; Online Loans; Financing